Interpretations of Wittgenstein philosophy - Solís, Yors (2015)
The following article presents and analyzes some of the most controversial and prominent interpretations that have been made about Wittgenstein’s philosophy. Not before without clarifying that for Wittgenstein himself, this work and the ones that will be discussed, would be senseless for him.